Physical chemistry : thermodynamics, statistical mechanics & kinetics - Cooksy, Andrew (Boston : Pearson, 2014)
In the phase transitions among the solid, liquid, and gaseous forms of water, we see a profound demonstration of how properties at the molecular scale dictate the behavior of the bulk material. As ice is heated beyond its melting point, new avenues for molecular motion become open to the energy being added. Upon entering the gas phase, the water molecules can explore new territory, unavailable to the liquid or solid. These transformations can be seen as a shifting balance between the forces that bind the molecules and the thermal energy that excites these motions--a window through thermodynamics on the intricate mechanisms that drive chemistry.
Classical physical chemistry sets the stage -- Introduction to statistical mechanics : Building up to the bulk -- Partitioning the energy -- Statistical mechanics and molecular interactions -- Mass transport : Collisions and diffusion -- Energy transport : Radiation and matter -- Introduction to thermodynamics : Heat capacity -- The first law : Expansion and engines -- The second and third laws : Entropy -- Phase transitions and phase equilibrium -- Solutions -- The thermodynamics of chemical reactions -- Chemical kinetics : Elementary reactions -- Chemical kinetics : Multi-step reactions.
Includes index.
Keywords: Chemistry, Physical and theoretical -- Textbooks; Thermodynamics -- Textbooks; Statistical mechanics -- Textbooks; Chemical kinetics -- Textbooks; Chemical kinetics; Chemistry, Physical and theoretical; Statistical mechanics; Thermodynamics; Textbooks